Modelo de apoio à decisão multicritério para avaliação de risco na cadeia de suprimentos em edificações - Chaves, Lárdner Gadelha (2020)
The study of the civil construction supply chain is an activity of fundamental importance. It is known that this chain presents a series of risks that impact the entire sector. For the management of the supply chain to be conducted efficiently, the stages of risk identification and assessment are considered. One way to carry out these activities is through Multiple Criteria Decision Aiding (MCDA). This research aims to propose a model to support multicriteria decision using the Fuzzy TOPSIS method to assess risks in the building supply chain in Fortaleza / CE. The methodology presents the survey and evaluation of uncertainties through bibliographic research and the opinion of decision makers, providing a model capable of hierarchizing the risks considering the impact in the areas of the chain (purchasing, internal logistics, inventory management, project execution), as well as the probability of occurrence and ease of detecting uncertainties. Thus, this work contributes effectively because it allows to understand real and complex problems faced in the construction industry, showing an accurate and objective result.